Synergistic Effects in Copolymerized Carbon Nitride/MoO3 Heterojunction Composites for Efficient Visible‐Light‐Driven Photocatalysis - Junsheng Ye; Abeer M. Beagan; Sheng‐Rong Guo; Asif Hayat; Yasin Orooji (EcoMat)
ABSTRACT The engineering of very effective and sustainable photocatalysts is needed to confront both environmental and energy problems. This work included the synthesis and evaluation of a range of copolymerized graphitic carbon nitride (CN)‐based materials (CN‐PAx) and their heterojunction composite materials with molybdenum trioxide (MoO3) for photocatalytic hydrogen (H2) generation and methylene blue (MB) degradation under visible‐light illumination. Pristine CN and MoO3 had lower photocatalytic performance, but copolymerized CN materials (CN‐PA200, CN‐PA400, CN‐PA600) and their heterojunction composite materials (CN/MoO3, CN‐PA400/MoO3(3%), CN‐PA400/MoO3(6%), and CN‐PA400/MoO3(9%)) demonstrated substantial enhancements. Of them, CN‐PA400/MoO3(6%) had the greatest H2 production rate of 127.22 μmol/h, almost 6.8 times higher than pure CN. It attained an outstanding MB photodegradation performance of 99.3% in 1 h, demonstrating exceptional stability by maintaining over 95% effectiveness throughout four successive cycles. The exceptional efficiency of CN‐PA400/MoO3(6%) is ascribed to its improved heterojunction design, which improves the separation of charge particles, minimizes recombination, and promotes visible‐light absorption. The band alignment among CN‐PA400 and MoO3 facilitates effective electron transport, whereas the presence of many active sites enhances the photocatalytic processes. These results present significant insights into the development of effective heterojunction photocatalysts and highlight the promise of CN‐PA400/MoO3(6%) for renewable energy generation and environmental cleanup purposes.